Nilai Pendidikan Karakter dalam Dongeng Tujuh Menit Karya Clara NG dan Relevansinya Bagi Anak Usia Madrasah Ibtidaiyah (MI) - Putri Puji Ayu Lestari (Journal on Education, 2022)
The purpose of this research is to analyze the educational values contained in Clara NG's 7-Minute Fairy Tale and its relevance in the world of children, especially in children of Madrasah Ibtidaiyah (MI) age. This research uses qualitative methods, which produce descriptive data. This study will analyze, analyze, and clarify the value of character education for MI-age children in 7-Minute Fairy Tales by focusing on the value of character education and its relevance to the values of character education for MI-age students